Try this at home [homeland security]. - Cass, S.
It's not just the government and big corporations that are turning to technology for help following 9/11. Fearful of an unexpected terrorist attack, many individuals are taking the phrase "homeland security" literally. They're buying the kind of products that before last year were generally found only in the cabinets of survivalists and militiamen. But will these products be of any use in a real emergency or are their makers simply playing on people's fears? One such device, the Raditect home gamma radiation detector and its use, is briefly outlined. Also mentioned are potassium iodide pills to aid in ridding the body of ingested radioactive iodine.
Keywords: Raditect home gamma radiation detector; Homeland security; Potassium iodide pills; Unexpected terrorist attack